Altered dorsal premotor-motor interhemispheric pathway activity in focal arm dystonia. - Koch, G; Schneider, S; Bäumer, T; Franca, M; Münchau, A; Cheeran, B; Fernandez del Olmo, M; Cordivari, C; Rounis, E; Caltagirone, C; Bhatia, K; Rothwell, J (2008)
Given the possible role of dorsal premotor cortex (PMd) in the pathophysiology of dystonia, we used transcranial magnetic stimulation (TMS) methods to study PMd and PMd-primary motor cortex (M1) interactions in patients with focal arm dystonia. Here, we tested the connectivity between left PMd and right M1 as well as the intracortical excitability of PMd in 11 right-handed patients with focal arm/hand dystonia and nine age-matched healthy controls. The results showed that excitability of the inhibitory connection between PMd and M1 was reduced in patients, but there was no significant difference to healthy subjects in the excitability of the facilitatory connection. A triple stimulation technique in which pairs of TMS pulses are given over PMd and their interaction measured in terms of the effect on the baseline PMd-M1 connection failed to reveal the usual pattern of interaction between the pairs of PMd stimuli. Indeed, the results in patients were similar to those seen in a group of young healthy subjects after the excitability of PMd had been changed by pretreatment with high-frequency rTMS. We suggest that reduced transcallosal inhibition from the PMd may be involved in the altered pattern of abnormal muscle contractions of agonists and antagonists (overflow).